2008
DOI: 10.1002/adfm.200800943
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport Properties of Ensembles of Perylene‐Substituted Poly‐isocyanopeptide Arrays

Abstract: The electronic transport properties of stacks of perylene‐bis(dicarboximide) (PDI) chromophores, covalently fixed to the side arms of rigid, helical polyisocyanopeptides, are studied using thin‐film transistors. In device architectures where the transistor channel lengths are somewhat greater than the average polymer chain length, carrier mobilities of order 10−3 cm2 V−1 s−1 at 350 K are found, which are limited by inter‐chain transport processes. The influence of π–π interactions on the material properties is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 45 publications
3
72
0
2
Order By: Relevance
“…This design strategy for the regulation of electronic behavior of organic conductive components would also apply to nonfullerene systems. 10,13 It can also be further coupled with the strategy of side-chain tuning, which helps to decrease the interchain transport, to capitalize the overall enhancement of charge transport in bulk. Moreover, these polymer thin lms showed excellent solvent resistance as a result of their high molecular weight despite their high solubility, making them potentially interesting in solution-processed device fabrications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This design strategy for the regulation of electronic behavior of organic conductive components would also apply to nonfullerene systems. 10,13 It can also be further coupled with the strategy of side-chain tuning, which helps to decrease the interchain transport, to capitalize the overall enhancement of charge transport in bulk. Moreover, these polymer thin lms showed excellent solvent resistance as a result of their high molecular weight despite their high solubility, making them potentially interesting in solution-processed device fabrications.…”
Section: Resultsmentioning
confidence: 99%
“…13 However, no enhancement of charge carrier mobility of such polymeric systems has been reported, compared to the corresponding monomer lm. There remains a challenge to achieve the close intramolecular contact between the conductive units and to maximize the electronic coupling between them using covalent control.…”
Section: 8mentioning
confidence: 99%
“…[6] In addition to the highly efficient migrational energy transfer observed in the pery-PIC system, [5] theoretical calculations have indicated that the high degree of ordering and electronic orbital overlap along the rigid PIC backbone result in large transfer integrals. [7] Commensurate investigations of the conductivity and carrier mobility, using thin-film transistor architectures, have also been recently reported. [7,8] Organic photovoltaics (OPVs) currently represent a key area of interest within research into renewable solar energy, [9][10][11] with state-of-the-art power conversion efficiencies of over 7% now being reported.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Commensurate investigations of the conductivity and carrier mobility, using thin-film transistor architectures, have also been recently reported. [7,8] Organic photovoltaics (OPVs) currently represent a key area of interest within research into renewable solar energy, [9][10][11] with state-of-the-art power conversion efficiencies of over 7% now being reported. [12] Great advances have been made regarding issues such as low bandgap and spectral matching, morphology, stability [13] and facility of processing.…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has focused on utilising the π-π interactions of perylene monomers for supramolecular assembles that display exciton transport, [30][31][32][33] the use of polymers as a spatial scaffold with controlled inter-chromophore spacing for organising dye molecules is one potential method of allowing higher PDI concentrations without aggregation. Incorporating a low concentration emitter species enables FRET and minimises reabsorption losses.…”
Section: Introductionmentioning
confidence: 99%